Strategy processes and practices: Dialogues and intersections - Burgelman, Robert A.; Floyd, Steven W.; Laamanen, Tomi; Maritere, Saku; Vaara, Eero; Whittington, Richard (Strategic Management Journal, 2018)
[Research summary: Building on our review of the strategy process and practice research, we identify three ways to see the relationships between the two research traditions: complementary, critical, and combinatory views. We adopt in this special issue the combinatory view, in which activities and processes are seen as closely intertwined aspects of the same phenomena. It is this view that we argue offers both strategy practice and strategy process scholars some of the greatest opportunities for joint research going forward. We develop a combinatory framework for understanding strategy processes and practices (SAPP) and based on that call for more research on (a) temporality, (b) actors and agency, (c) cognition and emotionality, (d) materiality and tools, (e) structures and systems, and (f) language and meaning.]